Capacidade fiscal e desenvolvimento no território: Bases para a articulaç\~ao federativa - Constantino Cronemberger Mendes; Ronaldo Ramos Vasconcellos; Luciléia Aparecida Colombo; Erika Amorim Araujo; Manuel Arantes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This study aims to analyze how the municipal capacity to provide public goods and services relates to social demands across diverse territorial contexts in Brazil. The research identifies four municipal typologies based on the intersection of fiscal capacity (per capita revenue) and sustainable development levels (IDSC): high-high, low-low, high-low, and low-high. These categories are distributed throughout the national territory and reflect distinct socioeconomic realities, each requiring tailored public policy approaches. The findings highlight the critical need for a national fiscal equalization system capable of aligning local revenue-generating capacities with socioeconomic demands. Despite the enhanced role granted to municipalities by the 1988 Federal Constitution, many - particularly in the North and Northeast regions - continue to face significant limitations in revenue collection and public policy implementation. The study advocates for recognizing the territory as a complementary unit of public action beyond the municipality itself, emphasizing the potential of intermunicipal and interstate consortia as cooperative governance arrangements. It concludes that the advancement of a more cooperative and equitable federalism hinges on overcoming institutional gaps and strengthening regional governance capacities. Finally, the research encourages further investigation into critical themes such as the effective participation of the federal government in public consortia and the broader implications of asymmetric federalism on policy design, coordination, and delivery at the subnational level.
Keywords: H71; H77; R58; 330; Brazilian federalism; fiscal capacity; territorial governance